Studi Environmental Health Risk Assessment (EHRA) Faktor yang Mendorong Perilaku Penggunaan Jamban Di Kabupaten Bondowoso Tahun 2018 - Wulandari Wulandari; Fx.Ady Soesetyo; Ancah Caesarina Novi M (Pascasarjana Universitas Jember, 2019)
In Indonesia the problem of sanitation is the problem of socio-cultural challenges. This also affected Bondowoso District which was in the first position of 38 Regencies or cities in East Java. So that the aim of the researcher is to describe and analyze the encouraging factors mainly focused on the role of health workers and the sanitation policy system. This study used a cross sectional design. The research location in Bondowoso Regency in November 2018. The population is 430 respondents spread across 7 sub districts. The result this study are the role of health workers with a significance value of 0,030 smaller than α. The sanitation policy system has significance value of 0,045 smaller than α. So, the conclution is the role of health workers and the sanitation policy system has to do with the behavior of using lavatory. Keyword: reinforcing factor, sanitation, role of health workers, the sanitation policy system.